Nutritional Variation of Different Feed Ingredients and Compound Feed Found in Different Parts of Nepal - Tiwari, MR; Khanal, SK; Shrestha, B; Jha, RK (Nepal Agriculture Research Journal, 2009)
Many feed industries in various parts of the country have been producing and marketingdifferent types of compound feeds. The source of feed ingredients also varies greatly which willultimately lead to the variation in the quality of finished products. Altogether 493 samples of 50different feed ingredients and compound feed were collected from Baglung, Baitadi, Banke,Chitwan, Darchula, Dolakha, Dolpa, Gorkha, Ilam, Jhapa, Kathmandu, Kaski, Lalitpur,Lamjung, Morang, Mahottary, Makwanpur, Myagdi, Nawal Parasi, Parbat, Parsa, Rasuwa,Rupandehi, Sankhuwasava, Sunsari, Saptari, Sarlahi, Sindhupalchok, Siraha, Syangja andTanahun districts. Highest content of dry matter (99.51%), organic matter (98.45%), total ash(98.14%) and crude protein (67.85%) was recorded for oyster cell, white maize grain, oyster celland meat meal respectively. Similarly, the rice husk was found to be superior in crude fibrecontent (34.46%) In terms of mineral oyster cell was found to be superior in calcium content(35.94%) and bone meal in phosphorous content (1.59%) as compared to other feed ingredients.Key words: Crude fibre; crude protein; dry matter; feed ingredients; organic matter; total ashDOI: 10.3126/narj.v7i0.1872Nepal Agriculture Research Journal Vol.7 2006 pp.75-81